Development of a Blockchain-Based Digital Data Identity Management System - Ardi Birawinata; Muhammad Nasir (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2026)
The management of student identity data requires a system that ensures data security, integrity, and transparency. Conventional data management methods are vulnerable to data redundancy and manipulation, particularly in educational institutions. This study aims to develop a blockchain-based digital identity data management system for SMK Bina Sriwijaya Palembang using the Prototyping development method. The Prototyping approach was selected to allow iterative system evaluation and validation, especially for complex Smart Contract logic. The system was implemented as a web-based application using React JS for the front-end and Node.js for the back-end, with Ethereum Smart Contracts developed in Solidity. Ganache was used as a local blockchain network for testing, while IPFS was integrated for decentralized storage of digital assets. The results show that the proposed system successfully secures student identity data, prevents unauthorized data manipulation, and improves the efficiency of data verification processes. This study demonstrates that blockchain technology combined with a prototyping approach can provide a reliable solution for digital identity management in educational environments.